Deexcitation Probabilities of Ne(3P2) by Ar for the Case E << D - Khadka, Deba Bahadur (Journal of Nepal Chemical Society, 2009)
The deexcitaion probability calculation of the total Penning ionization cross section for Ne(3P2) by Ar has been made in the region of the collisional energy from 18.5 to 38.1 meV. Comparing the magnitude of the mean collisional energy with respect to D, the application of the analysis in the case E >> D is expected to be more appropriate than in the case E << D. More advance theoretical investigations for Ne(3P2) by Ar should consider the further understanding. Keywords: Deexcitation cross section; Collisional energy; Pulse radiolysis method; Metastable atoms; Impact parameter. DOI: 10.3126/jncs.v24i0.2382 Journal of Nepal Chemical Society, Vol. 24, 2009 Page: 19-23